Hazara's Discrimination Reflected In Khaled Hosseini'sThe Kite Runner Novel (2003): A Sociological Approach - Fuadina, Nur Syifa', Drs. Abdillah Nugroho, M.Hum, Drs. Sigit Haryanto, M.Hum (2013)
This study is about Hazara's Discrimination Reflected in Khaled Hosseini's The Kite Runner Novel (2003) by using a sociological approach. The objectives of the study are to analyze the novel based its structural elements and to describe the novel based on the sociological approach. The researcher uses qualitative method to analyze the novel. The object of the study is The Kite Runner Novel that consists of twenty five chapters and 215 pages. It is analyzed through Sociological Approach. The primary data is taken from the novel itself and the secondary data sources are books or any information that are relevant to the subject matter. The techniques of the data are reading the novel repeatedly, taking notes of important parts both primary and secondary data, arranging the data into several groups based on its theoretical category, selecting particular parts considered important and relevant for analysis, drawing conclusion and formulate its pedagogical suggestion. The techniques of data analysis are as follows: the first is analyzing the data based on its structural elements, focuses paid on the structural analysis of the novel, the second step is analyzing the data based in Sociological Approach, and focuses paid on the meaning of Hazara's discrimination. The conclusions of study are, first based on structural analysis of each element, it shows that the character and characterization, setting, plot, point of view, style, and theme are related to each other and form the unity into good quality of novel. It conveys a message that the racial injustice must be crashed, because all people of all races are equal in the law. Second, based on Sociological Approach, the conclusion is that there is racial discrimination in The Kite Runner novel. Khaled Hosseini shows that Hazara get the discrimination from Pashtun or soldier of Taliban in Kabul, Afghanistan.